Potential of ferritin 2 as an antigen for the development of a universal vaccine for avian mites, poultry red mites, tropical fowl mites, and northern fowl mites - Win, Shwe Yee; Murata, Shiro; Fujisawa, Sotaro; Seo, Hikari; Sato, Jumpei; Motai, Yoshinosuke; Sato, Takumi; Oishi, Eiji; Taneno, Akira; Htun, Lat Lat; Bawm, Saw; Okagawa, Tomohiro; et al. (Frontiers in Veterinary Science, 2023)
Introduction Poultry red mites (PRMs, Dermanyssus gallinae), blood-sucking ectoparasites, are a threat to the poultry industry because of reduced production caused by infestation. In addition, tropical fowl mites (TFMs, Ornithonyssus bursa) and northern fowl mites (NFMs, Ornithonyssus sylviarum) are hematophagous, distributed in various regions, genetically and morphologically close to PRMs, and cause similar problems to the poultry industry. Vaccine approaches have been studied for PRM control, and several molecules have been identified in PRMs as candidates for effective vaccine antigens. The development of an anti-PRM vaccine as a universal vaccine with broad efficacy against avian mites could improve the productivity of poultry farms worldwide. Molecules that are highly conserved among avian mites and have critical functions in the physiology and growth of mites could be ideal antigen candidates for the development of universal vaccines. Ferritin 2 (FER2), an iron-binding protein, is critical for the reproduction and survival of PRMs and has been reported as a useful vaccine antigen for the control of PRMs and a candidate for the universal vaccine antigen in some tick species. Method and results Herein, we identified and characterized FER2 in TFMs and NFM. Compared with the sequence of PRM, the ferroxidase centers of the heavy chain subunits were conserved in FER2 of TFMs and NFMs. Phylogenetic analysis revealed that FER2 belongs to clusters of secretory ferritins of mites and other arthropods. Recombinant FER2 (rFER2) proteins from PRMs, TFMs, and NFMs exhibited iron-binding abilities. Immunization with each rFER2 induced strong antibody responses in chickens, and each immune plasma cross-reacted with rFER2 from different mites. Moreover, mortality rates of PRMs fed with immune plasma against rFER2 from TFMs or NFMs, in addition to PRMs, were higher than those of control plasma. Discussion rFER2 from each avian mite exhibited anti-PRM effects. This data suggests that it has the potential to be used as an antigen candidate for a universal vaccine against avian mites. Further studies are needed to access the usefulness of FER2 as a universal vaccine for the control of avian mites.